Eleutheroside B alleviates oxidative stress and neuroinflammation by inhibiting the JAK2/STAT3 signaling pathway in a rat high altitude cerebral edema model - He, Yacong; Zhang, Hongying; Zhang, Xiu; Han, Yue; Duan, Huxinyue; Song, Wenqian; Tian, Qingqing; Wang, Yilan; Li, Guang; Wu, Chunjie; Wang, Zhenxing; Zhao, Tianzhu (Frontiers in Pharmacology, 2024)
Background: High altitude cerebral edema (HACE) is a condition where the central nervous system experiences severe impairment as a result of sudden oxygen deprivation at high elevations. At present, effective measures for preventing and treating this condition are still lacking. Eleutheroside B (EB), the primary natural active compound found in the Eleutheroside senticosus, has demonstrated various biological functions. It has also shown significant potential in addressing acute mountain sickness and various neurological disorders. However, additional investigation is required to explore the potential protective effects and its underlying mechanisms of EB on HACE.The male rats received pre-treatment with either vehicle, EB 100 mg/kg or 50 mg/kg, Dexamethasone 4 mg/kg, or coumermycin A1 100 μg/kg. To simulate the hypobaric hypoxia environment at a plateau of 6000 meters, a hypobaric hypoxia chamber was utilized. The therapeutic effects of EB were assessed through measurements of brain water content, histopathological observation, and evaluation of oxidative stress and inflammatory factors using immunofluorescence and ELISA. Furthermore, molecular docking, molecular dynamics simulation and Western blot were employed to clarify its molecular mechanism. Through these analyses, the underlying mechanism by which EB on HACE was identified.Results: Pre-treatment with EB demonstrated a significant protective effect against HACE by effectively reducing brain water content, down-regulating HIF-1α and AQP4 protein expression induced by hypoxia and reversing pathological changes in brain tissue and neuron damage. Compared to the group treated with HACE alone, the group pre-treated with EB showed a significant reduction in levels of ROS and MDA, as well as an increase in GSH. In addition, pre-treatment with EB led to a significant decrease in the levels of IL-1β, IL-6, and TNF-α. Molecular docking and dynamics simulations indicated that EB has a strong binding affinity to the JAK2/STAT3 signaling pathway. Western blot further confirmed that EB significantly down-regulated the expression of JAK2/STAT3 related proteins in the brain tissue of HACE rats. Additionally, coumermycin A1, an agonist of the JAK2, reversed the anti-oxidative stress and neuroinflammation against HACE of EB.EB exerts its antioxidant stress and anti-neuroinflammatory effects by inhibiting the JAK2/STAT3 signaling pathway in a rat HACE model.